2021
DOI: 10.1093/noajnl/vdab019
|View full text |Cite
|
Sign up to set email alerts
|

[18F]-FDHT PET/CT as a tool for imaging androgen receptor expression in high-grade glioma

Abstract: Background Glioblastoma (GBM) is associated with poor overall survival. Recently, we showed that androgen receptor (AR) protein is overexpressed in 56% of GBM specimens and AR antagonists induced dose-dependent death in several GBM cell lines and significantly reduced tumor growth and prolonged the lifespan of mice implanted with human GBM. 16β-18F-fluoro-5α-dihydrotestosterone ([18F]-FDHT) is a PET tracer used to detect AR expression in prostate and breast cancers. This study was aimed at ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
(12 reference statements)
2
13
0
Order By: Relevance
“…Our observations of different levels of AR protein expression in different GBM tumor structures indirectly confirm the results of the study by Orevi et al [ 31 ]. In their work, the authors used imaging to identify AR-positive gliomas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observations of different levels of AR protein expression in different GBM tumor structures indirectly confirm the results of the study by Orevi et al [ 31 ]. In their work, the authors used imaging to identify AR-positive gliomas.…”
Section: Discussionsupporting
confidence: 92%
“…However, this may be due to different post-transcriptional processes in these structures. This assumption is supported by the observation of Zalcman et al [ 22 ] and Orevi et al [ 31 ], who found no correlation between AR mRNA and AR protein expressions.…”
Section: Discussionsupporting
confidence: 55%
“…The overexpression of androgen receptor (AR) is demonstrated in the majority of glioblastoma multiforme (GBM) specimens; Shamni et al [1,5] evaluated whether 16β-18 Ffluoro-5α-dihydrotestosterone ([ 18 F]-FDHT) could detect and quantify AR expression in GBM patients, in order to select candidates who might benefit from AR antagonist therapy. Preliminary results in 12 patients indicate that [ 18 F]-FDHT PET/CT might be a helpful tool for selecting those patients, also allowing treatment response evaluation.…”
Section: Innovationmentioning
confidence: 99%
“…They are easily affected by certain objective factors, such as the doctor's experience, mental state, and the quality of CT imaging. This is not only time-consuming and labor-intensive but also causes risk of misdiagnosis and missed diagnosis [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%